2023
DOI: 10.1093/mnras/stad438
|View full text |Cite
|
Sign up to set email alerts
|

Radio-bright versus radio-dark gamma-ray bursts – more evidence for distinct progenitors

Abstract: We analyze two distinct samples of GRBs, with and without radio afterglow emission. We use an updated sample of 211 GRBs and find, in agreement with previous results (although with a sample that is almost twice as large), that the intrinsic γ-ray duration (Tint) and isotropic equivalent energy (Eiso) distributions between these two populations appear to be significantly different. This implies that the radio-bright GRBs are more energetic and last longer than radio-dark GRBs. The two samples’ redshift distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Lloyd-Ronning et al (2019b) confirmed this in a subsample of radio-bright GRBs with isotropic equivalent energies above 10 52 erg. Recently Chakraborty et al (2023) further confirmed this trend, employing different techniques to account for data selection effects that could have artificially produced this intrinsic duration-redshift anticorrelation.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Lloyd-Ronning et al (2019b) confirmed this in a subsample of radio-bright GRBs with isotropic equivalent energies above 10 52 erg. Recently Chakraborty et al (2023) further confirmed this trend, employing different techniques to account for data selection effects that could have artificially produced this intrinsic duration-redshift anticorrelation.…”
Section: Introductionmentioning
confidence: 79%
“…In their radio-bright subsample consisting of 79 GRBs, they found a ∼5σ correlation (p-value ∼ 5 × 10 −5 ), with T int ∝ (1 + z) −1.4±0.3 . Recently, Chakraborty et al (2023) reanalyzed this correlation with an updated, larger sample of radio-bright and radio-dark GRBs, using a variety of approaches to account for selection effects. Even with fairly stringent and conservative assumptions about the biases, they found the correlation still exists, with T int ∝ (1 + z) −1.3±0.3 (p-value of 10 −6 ) for the radio-bright GRB sample and T int ∝ (1 + z) −1.2±0.4 (p-value of 10 −3 ) for the radio-dark sample.…”
Section: Lloydmentioning
confidence: 99%
See 1 more Smart Citation
“…This will provide a The previous studies have found that E iso , L iso , and θ jet are affected by redshift evolution and selection biases (Lloyd-Ronning et al 2002;Wei & Gao 2003;Yonetoku et al 2004;Zhang et al 2014;Lloyd-Ronning et al 2019;Guo et al 2020;Liu et al 2021;Chakraborty et al 2023). A nonparametric τ statistical technique has been widely used to resolve this problem (Lynden-Bell 1971;Lloyd-Ronning et al 2002;Wei & Gao 2003;Yonetoku et al 2004;Dainotti et al 2013;Zhang et al 2014;Lloyd-Ronning et al 2019;Dainotti et al 2021;Liu et al 2021;Chakraborty et al 2023). In order to separate the…”
Section: Three-parameter Correlationsmentioning
confidence: 99%
“…The values E iso,c ≡ E iso /g k (z), L iso,c ≡ L iso /g k (z), and θ jet,c ≡ θ jet /g k (z) represent the isotropic energy, peak luminosity, and opening angle after removing the evolution effect, respectively. For the SGRB sample, we take k E = 5.79 (Liu et al 2021), k L = 4.78 (Guo et al 2020), and k θ = 1.45 (Chakraborty et al 2023). Because the data of the LGRB sample are mainly from the Konus-Wind instrument, we take k E = 1.73 and k L = 3.24 from Xue et al (2019) for LGRBs.…”
Section: Three-parameter Correlationsmentioning
confidence: 99%